2016
DOI: 10.5603/kp.a2015.0117
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of high risk of non-adherence to antiplatelet treatment

Abstract: A b s t r a c tBackground: Dual antiplatelet therapy with acetylsalicylic acid (ASA) and clopidogrel is the standard of care for secondary prevention. Premature discontinuation of clopidogrel is associated with an increased risk of myocardial infarction (MI) or death, and greater health care expenditure. Aim:To develop an objective method for identification of patients with high risk of non-adherence to clopidogrel after MI. Methods:A total of 189 patients were enrolled into a prospective, observational, singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…Diabetes mellitus is associated with a chronic inflammatory state promoting platelets hyperactivity [19,20]. Several studies showed resistance to a conventional antiplatelet therapy with aspirin and clopidogrel in diabetic patients [2,20]. Prasugrel has been proven to be more effective than clopidogrel in both diabetic and non-diabetic subjects [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus is associated with a chronic inflammatory state promoting platelets hyperactivity [19,20]. Several studies showed resistance to a conventional antiplatelet therapy with aspirin and clopidogrel in diabetic patients [2,20]. Prasugrel has been proven to be more effective than clopidogrel in both diabetic and non-diabetic subjects [21].…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy (DAT) with aspirin and one of the platelet P2Y12 receptor antagonists reduces the risk of thrombotic events. This treatment is recommended in the management of patients with ACS and in patients after stent implantation [2][3][4]. Many reports have demonstrated excessive variability in response to clopidogrel, the most commonly used P2Y12 receptor antagonist, with a substantial rate of high on-treatment platelet reactivity (HTPR) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Nurse judgement of low discharge readiness was associated with a six-to nine-fold increase in readmission risk; however, patient self-assessment was associated neither with readmission nor with visits in emergency department [19]. Patient self-assessment is a purely subjective assessment, while nurse evaluation is more objective [20,21]. Such an approach was applied in RHD MIS in the first and second subscale.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the knowledge of reasons of this phenomenon as well as identification of barriers and problems in cooperation between patients and health care professionals is crucial for implementation of tailored educational interventions [79][80][81][82].…”
Section: Expert Opinionmentioning
confidence: 99%